A Comprehensive Membrane Interactome Mapping of Sho1p Reveals Fps1p as a Novel Key Player in the Regulation of the HOG Pathway in S. cerevisiae. Issue 11 (5th June 2015) - Lam, Mandy Hiu Yi; Snider, Jamie; Rehal, Monique; Wong, Victoria; Aboualizadeh, Farzaneh; Drecun, Luka; Wong, Olivia; Jubran, Bellal; Li, Meirui; Ali, Mehrab; Jessulat, Matthew; Deineko, Viktor; et al.
Abstract: Sho1p, an integral membrane protein, plays a vital role in the high-osmolarity glycerol (HOG) mitogen-activated protein kinase pathway in the yeast Saccharomyces cerevisiae . Activated under conditions of high osmotic stress, it interacts with other HOG pathway proteins to mediate cell signaling events, ensuring that yeast cells can adapt and remain viable. In an attempt to further understand how the function of Sho1p is regulated through its protein–protein interactions (PPIs), we identified 49 unique Sho1p PPIs through the use of membrane yeast two-hybrid (MYTH), an assay specifically suited to identify PPIs of full-length integral membrane proteins in their native membrane environment. Secondary validation by literature search, or two complementary PPI assays, confirmed 80% of these interactions, resulting in a high-quality Sho1p interactome. This set of putative PPIs included both previously characterized interactors, along with a large subset of interactors that have not been previously identified as binding to Sho1p. The SH3 domain of Sho1p was found to be important for binding to many of these interactors. One particular novel interactor of interest is the glycerol transporter Fps1p, which was shown to require the SH3 domain of Sho1p for binding via its N-terminal soluble regulatory domain. Furthermore, we found that Fps1p is involved in the positive regulation of Sho1p function and plays a role in the phosphorylation of the downstream kinase Hog1p. This study represents the largest membrane interactome analysis of Sho1p to date and complements past studies on the HOG pathway by increasing our understanding of Sho1p regulation. Graphical abstract: Highlights: Membrane yeast two-hybrid (MYTH) screens found new interactors of Sho1p (HOG pathway). Of the 49 putative interactors, 80% were confirmed by at least one other method. The glycerol transporter Fps1p binds the SH3 domain of Sho1p through its N-terminus. Fps1p is key for downstream signaling in the Sho1p-mediated branch of the HOG pathway. Our work resulted in the largest confirmed interactome for Sho1p to date.